KUALITAS JASA DAN KEPUASAN MAHASISWA PERGURUAN TINGGI SWASTA DI MALANG - Rahayu, Yayuk Sri (IQTISHODUNA, 2008)
In globalization era, the company must have the ability to satisfy their customer to be the winner of business competitiosince customer satisfaction depends on product or service quality. The purpose of this research is to find student’s assessment about service quality that was given by private universities in Malang and what kind of service quality attributes which has  less performance based on student expectation. This research used purposive and accidental sampling and analysis instrument is Importance-Performance Analysis. The results show, first, level of received service quality is still under level of student expectation so they are unsatisfied  second, there are four attributes which has less performance than student expectation that are the accuration of lecturer assessment, the willingness of lecturer and staff to listen and receive suggestion from students, meeting lecturer easily, and lecturer and staff serve students well. Therefore, based on  this result, private universities in Malang have to make this four attributes as a major priority in continous improvement of quality program to win competition.